Draft Genome Analysis Offers Insights Into the Mechanism by Which Streptomyces chartreusis WZS021 Increases Drought Tolerance in Sugarcane - Wang, Zhen; Solanki, Manoj Kumar; Yu, Zhuo-Xin; Yang, Li-Tao; An, Qian-Li; Dong, Deng-Feng; Li, Yang-Rui (Frontiers in Microbiology, 2019)
Drought directly affects sugarcane production. Plant growth-promoting bacteria have gained attention as growth promoters of plants under abiotic stresses. The present study focused on genome assessment of the plant-beneficial endophyte Streptomyces chartreusis WZS021 and its vital role in sugarcane plants under drought stress. Based on in-vitro plant growth-promoting trait analyses, WZS021 had multiple abilities, including tolerance to drought and production of 1-aminocyclopropane-1-carboxylic deaminase, siderophores, and indole acetic acid. We confirmed root colonization of sugarcane transplants by WZS021 by a sterile sand assay and scanning electron microscopy. Plants inoculated with strain WZS021 had a positive influence on the root parameters such as length and biomass when compared to the control plants. A comparative study of the responses of two sugarcane varieties (ROC22 and B8) to different levels of drought stress in the presence or absence of WZS021 was conducted by assessing the plant chemistry. The expression of antioxidants in sugarcane leaves varied with water stress level. WZS021 inoculation improved the contents of chlorophyll, proline, and phytohormones, revealing some potential the mechanisms by which this strain improves drought tolerance in sugarcane plants. We identified several genes that might be involved in the plant growth- and drought tolerance-promoting effects of this strain.